KONTRIBUSI KEPEMIMPINAN KEPALA SEKOLAH ISLAM BERBASIS SERVANT LEADERSHIP TERHADAP DAYA SAING DAN SPMB - Sultan Syah; Akhmad Shunhaji; Abd. Aziz (Berajah Journal, 2026)
This study aims to examine the role of Islamic school principals’ leadership oriented toward servant leadership in enhancing school competitiveness while supporting the successful implementation of the Student Admission System (SPMB). This research employs a qualitative approach using a case study method at an Islamic educational institution. Data were collected through in-depth interviews, field observations, and document analysis, involving various stakeholders such as the principal, teachers, educational staff, and parents of students. The collected data were analyzed through processes of data reduction, data display, and conclusion drawing, and their validity was ensured through source and technique triangulation. The results reveal that the leadership of Islamic school principals who apply servant leadership values such as trustworthiness (amanah), service (khidmah), exemplary conduct, and empowerment plays a significant role in improving the quality of educational services and strengthening the school’s positive image in the community. Efforts to enhance competitiveness are carried out through strengthening academic quality, instilling Islamic values, and developing innovative flagship programs that align with community needs. These efforts have led to increased public trust, as reflected in the rising number of applicants and the improved quality of prospective students in the SPMB process. Therefore, this study confirms that servant leadership-based Islamic school leadership is an effective strategy for enhancing school competitiveness and ensuring the success of student admissions.